Raising Roma Educational Participation and Achievement: Collaborative Relationships, Transformative Change, and a Social Europe (Alberta Journal of Educational Research, 2016)
The paper gives an overview of Roma, Gypsy and Traveller (RGT) educational exclusion in the European Union and seeks to provide insights into good practice through case studies focusing on Bulgaria and the UK. The paper makes a case for the promotion of collaborative relationships, where RGT communities are active partners in developing curricula and decision-making in school. It is argued in the paper that such action needs to be made in tandem with interventionist and redistributive policy frameworks at the national and European level.Cet article offre un aperçu général de l’exclusion éducative pour les Roms, les Tsiganes et les gens du voyage (RTG) dans l’union européenne et cherche à éclairer les meilleures pratiques en se penchant sur des études de cas portant sur la Bulgarie et le Royaume-Uni. Cet article fait la promotion de relations de collaboration au sein desquels les communautés RTG constituent des partenaires actifs dans le développement des programmes d’études et des prises de décisions à l’école. L’article fait valoir qu’une telle démarche doit être accompagnée de cadres de politiques interventionnistes et redistributives aux échelles nationales et européennes.